European Breast Cancer Council manifesto 2018: Genetic risk prediction testing in breast cancer. (January 2019) - Rutgers, Emiel; Balmana, Judith; Beishon, Marc; Benn, Karen; Evans, D. Gareth; Mansel, Robert; Pharoah, Paul; Perry Skinner, Victoria; Stoppa-Lyonnet, Dominique; Travado, Luzia; Wyld, Lynda
Abstract: European Breast Cancer Council manifesto and supporting article on genetic risk prediction testing in breast cancer, presented at the 11th European Breast Cancer Conference in Barcelona, Spain. Highlights: Genetic tests that predict breast cancer risk are now widely available. The results of such tests can be complex and misinterpreted. Tests must be interpreted by appropriate healthcare professionals. Informed consent and counselling must be available. Awareness of tests and referrals must be promoted among healthcare professionals.